2012
DOI: 10.1111/j.1447-0594.2012.00840.x
|View full text |Cite
|
Sign up to set email alerts
|

Pleasant physical exercise program for prevention of cognitive decline in community‐dwelling elderly with subjective memory complaints

Abstract: Participants with subjective memory complaints who continued the pleasant physical exercise programs for 12 weeks showed improvement in some aspects of cognitive function. Participation of senior citizen volunteers enabled smooth implementation of the program, and alleviated the burden on the professional staff. The pleasant physical exercise intervention described in the present study could be regarded as a community-led intervention to prevent cognitive decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 22 publications
(39 reference statements)
1
24
0
1
Order By: Relevance
“…Therefore, to promote care prevention for community‐dwelling older people, it may be useful to improve their physical function. Physical activity interventions for older people have been reported to promote physical function, which prevents falls, and improves cognitive function . Such approaches have been used by care prevention programs based on the long‐term care insurance system in a large number of intervention studies .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to promote care prevention for community‐dwelling older people, it may be useful to improve their physical function. Physical activity interventions for older people have been reported to promote physical function, which prevents falls, and improves cognitive function . Such approaches have been used by care prevention programs based on the long‐term care insurance system in a large number of intervention studies .…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have developed different cognitive function training methods as countermeasures to prevent cognitive impairment and have reported their effects [1]. Other investigators also have reported the effects of physical exercise training on cognitive functions among elderly individuals [2,3]. Additionally, Hillman et al and Silsupado have indicated that executive cognitive functions, which are related to the control of goal-oriented actions and adaptive behaviors, are strongly impaired by aging and respond positively to exercise training [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there are some community-based care programs for older adults. Some older adults with subjective memory complaints who continued the pleasant physical exercise programs showed improvement in some aspects of cognitive function [15]. In addition, the cognitive behavioral group program is currently made available in geriatric care settings nationwide in The Netherlands [16].…”
Section: Introductionmentioning
confidence: 99%